Competence of university teachers in organizing and conducting distance learning at a university - Avdeeva, Tatyana (2022)
Distance learning is a form of education that is perfectly suitable for the implementation of contemporary models of education in the information society. This fact relates to the tremendously progressive development of information technology and the increasingly more promising prospects for education. The present study aims to analyze the influence of professional self-improvement on the effectiveness of teachers’ work in the distance mode. Based on an empirical study using the survey method, the levels of competencies comprising competence in the organization and conduct of distance learning among teachers in the information-technical and pedagogical sphere are identified. The results obtained testify to the need to improve the pedagogical qualifications of teachers in the direction of improving competence in the field of information computer technologies and their application in education, as well as in the field of Internet technologies and distance learning.